2014
DOI: 10.15835/buasvmcn-hort:10278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of some Vitis vinifera L. Indigenous Varieties by Analysis of Leaf Photosynthetic Pigments

Abstract: Chlorophyll content in leaves of 11 Vitis vinifera L. indigenous varieties (Iasi vineyard, Romania) was determined by two independent methods: spectrophotometry (extraction) and with a OptiSciences CCM-200 plus chlorophyll content meter (non-destructive method) with the aim of comparing the results. Also, this study was conducted to establish the values of chlorophyll a/ chlorophyll b and chlorophyll/carotenoid ratio in middle leaves of vine stocks, in the phenophase of progressive growing of shoots. Area and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Compared to spectrophotometry, CCM-200 plus affords fast, reliable chlorophyll content measurements, although it does not provide details regarding chlorophyll components and ratios (Filimon et al, 2014). According to Van den Berg and Perkins (2004), small differences in the structures of the two main chlorophylls (a and b) produce differences in their absorption maxima, which help in their individual assay.…”
Section: Chlorophyll Content Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to spectrophotometry, CCM-200 plus affords fast, reliable chlorophyll content measurements, although it does not provide details regarding chlorophyll components and ratios (Filimon et al, 2014). According to Van den Berg and Perkins (2004), small differences in the structures of the two main chlorophylls (a and b) produce differences in their absorption maxima, which help in their individual assay.…”
Section: Chlorophyll Content Indexmentioning
confidence: 99%
“…Previous research conducted on different species showed significant linear correlation of total chlorophyll (by spectrophotometry) and chlorophyll content index (CCI) values, although with large differences in terms of data correlation (Van den Berg & Perkins, 2004;Ghasemi et al, 2011;Khaleghi et al, 2012;Callejas et al, 2013). The lack of a more consistent relationship between total chlorophyll by extraction and CCI values (non-destructive) for different V. vinifera L. genotypes and in different phenophases limits the potential use of the CCM-200 plus instrument for this specie (Filimon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%